Conservation of Chure Forest in Nepal: Issues, Challenges and Options - Pokhrel, Kabi Prasad (Economic Journal of Nepal, 2015)
Chure region has a distinct geographical and bio-physical specificities lying on the foothill of Himalaya. It is the youngest mountain of the world, and suffering from mass erosion, landslides and other environmental externalities which make the region vulnerable. Resource depletion, for example deforestation, due to natural as well as human induces factors in the Chure region has accelerated, and livelihood opportunities have been retreating. Degradation of watershed, lowering the underground water and disturbing the ecological niche in and around the region makes the region more sensitive and fragile. Government has given greater emphasis on the protection of Chure through initiation of ‘Rastrapati Chure Conservation Program' since 2009. It is an attempt to identify the problems, challenges and issues of Chure forest conservation and to propose an effective conservation plan using qualitative as well as quantitative methods of analysis. The ecological, geographical, and bio-physical conditions of the Chure region have rapidly degrading since last 32 years. Increasing landslides and flooding, and human intervention makes Chure more fragile and weakest zone where lacks/inadequate of livelihood assets and food insecurity are noted. However, Chure region has many opportunities of employment and income generation through establishment of environment friendly green enterprises. Thus it is an urgent need to formulate short-term to long-term strategies with policy priorities actions and result-oriented efforts in order to establish Chure as a rich bio-diversity zone, with hazardless and improved livelihoods of its people.The Economic Journal of NepalVol. 35, No. 4, October-December 2012 (Issue N0. 140)Page : 262-278